Whole transcriptome analysis of HCT-8 cells infected by Cryptosporidium parvum - Lulu Sun; Juanfeng Li; Fujie Xie; Shanbo Wu; Tianren Shao; Xiaoying Li; Junqiang Li; Fuchun Jian; Sumei Zhang; Changshen Ning; Longxian Zhang; Rongjun Wang (Parasites & Vectors, 2022)
Abstract Background Cryptosporidium species are zoonotic protozoans that are important causes of diarrhoeal disease in both humans and animals. Non-coding RNAs (ncRNAs) play an important role in the innate immune defense against Cryptosporidium infection, but the underlying molecular mechanisms in the interaction between human ileocecal adenocarcinoma (HCT-8) cells and Cryptosporidium species have not been entirely revealed. Methods The expression profiles of messenger RNAs (mRNAs), long non-coding RNAs (lncRNAs), microRNAs (miRNAs) and circular RNAs (circRNAs) in the early phase of infection of HCT-8 cells with Cryptosporidium parvum and at 3 and 12 h post infection were analyzed using the RNA-sequencing technique. The biological functions of differentially expressed RNAs (dif-RNAs) were discovered through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. The targeting relationships between three ncRNAs and mRNAs were analyzed using bioinformatics methods, followed by building a competing endogenous RNA (ceRNA) regulatory network centered on miRNAs. Results After strictly filtering the raw data, our analysis revealed 393 dif-lncRNAs, 69 dif-miRNAs and 115 dif-mRNAs at 3 hpi, and 450 dif-lncRNAs, 129 dif-miRNAs, 117 dif-mRNAs and one dif-circRNA at 12 hpi. Of these, 94 dif-lncRNAs, 24 dif-miRNAs and 22 dif-mRNAs were detected at both post-infection time points. Eleven dif-lncRNAs, seven dif-miRNAs, eight dif-mRNAs and one circRNA were randomly selected and confirmed using the quantitative real-time PCR. Bioinformatics analyses showed that the dif-mRNAs were significantly enriched in nutritional absorption, metabolic processes and metabolism-related pathways, while the dif-lncRNAs were mainly involved in the pathways related to the infection and pathogenicity of C. parvum (e.g. tight junction protein) and immune-related pathways (e.g. cell adhesion molecules). In contrast, dif-miRNAs and dif-circRNA were significantly enriched in apoptosis and apoptosis-related pathways. Among the downregulated RNAs, the miRNAs has-miR-324-3p and hsa-miR-3127-5p appear to be crucial miRNAs which could negatively regulate circRNA, lncRNA and mRNA. Conclusions The whole transcriptome profiles of HCT-8 cells infected with C. parvum were obtained in this study. The results of the GO and KEGG pathway analyses suggest significant roles for these dif-RNAs during the course of C. parvum infection. A ceRNA regulation network containing miRNA at its center was constructed for the first time, with hsa-miR-324-3p and hsa-miR-3127-5p being the crucial miRNAs. These findings provide novel insights into the responses of human intestinal epithelial cells to C. parvum infection. Graphical Abstract